FRAUD PENTAGON THEORY FOR DETECTING FINANCIAL STATEMENT FRAUDULENT - Rif'atul Fitriyah; Santi Novita (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2021)
Cases of fraud from 2019 to 2020 in Indonesia involve companies of state-owned enterprises. This study aimed to analyze the factors that encourage financial statement fraudulent with analysis of fraud pentagon theory. This research analyzes the influence of variable pressure proxied by financial stability, opportunity proxied by auditor change, rationalization proxied by audit opinion, capability proxied by change of directors and arrogance proxied by the number of CEO’s. This reserach uses 100 of State-Owned Enterprises companies listed on Indonesia Stock Exchange in the period 2015-2019. Data analyzed by using logistic regression. The results showed that pressure and opportunity influence the financial statement fraudulent, while rationalization, capability, and arrogance have not.